Research on Analysis of Schopenhauer's Pessimistic Philosophy - Wang, Keqiong (International Journal of Social Sciences and Public Administration, 2024)
Schopenhauer established his own philosophical system of pessimism based on the theory of willpower and the theory of representation. Schopenhauer believed that the world, like man, was a complete will and appearance, and that nothing else was left. Will is the appearance of the world, the will itself does not recognize, the will is mainly through the appearance of the world to understand their own demands. On the issue of life, Schopenhauer's philosophy shows a kind of understanding and sympathy for life. The existence of people's desire is a painful thing, but people should have the courage to face the pessimistic life, and keep a clear mind in the process of survival, grow up in self-education, in order to pursue the highest realm of intelligent life.